PARTISIPASI MASYARAKAT DALAM PENYELENGGARAAN SHALAT JENAZAH DI DUSUN HARAPAN MAJU JORONG AMPANG GADANG KECAMATAN PANTI KABUPATEN PASAMAN - Kartina Kartina; Muhiddinur Kamal; Wedra Aprison; Charles Charles (Universitas Pahlawan Tuanku Tambusai, 2022)
The background of the problems found, the community just stood outside the mosque without participating in praying the corpse, and some of them thought that the funeral prayer was not too important because they saw from the law that the funeral prayer was fardu kifayah. In addition, people often ask for help from religious leaders to become prayer priests because the deceased's family cannot perform the funeral prayer, because according to them the reading of the funeral prayer is difficult to memorize. This study aims to see how the forms of community participation and the inhibiting factors of community participation in organizing the funeral prayer. The approach used in this study is a qualitative approach, meaning that researchers will see phenomena that occur in society. In this study using a form of qualitative descriptive research. Based on the findings of data analysis, several conclusions can be drawn, namely the form of community participation in the implementation of the funeral prayer is still low, caused by work, laziness and lack of knowledge about reading the funeral prayer. Although religious leaders have provided motivation in the form of recitations every Sunday. The inhibiting factors for community participation in the implementation of the funeral prayer are the feeling of laziness caused by being tired of working, considering the funeral prayer to be unimportant, and not being too close to the person who died. Keywords: Society participation, funeral prayer